A Multiple Bits Watermark for Relational Data - LI, Yingjiu (Institutional Knowledge at Singapore Management University, 2008)
At the heart of the information economy, commercially and publicly useful databases must be sufficiently protected from pirated copying. Complementary to the Database Protection Act, database watermarking techniques are designed to thwart pirated copying by embedding owner-specific information into databases so that the ownership of pirated copies of protected databases can be claimed if the embedded information is detected. This article presents a robust watermarking scheme for embedding a multiple-bits watermark to numerical attributes in database relations. The scheme is robust in the sense that it provides an upper bound for the probability that a valid watermark is detected from unmarked data, or a fictitious secret key is discovered from pirated data. This upper bound is independent of the size of the data. The scheme is extended to database relations without primary-key attributes to thwart attribute-related attacks. The scheme is also extended to multiple watermarks for defending additive attacks and for proving joint ownership.